2023
DOI: 10.3389/fonc.2023.1113346
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness analysis of serplulimab versus regorafenib for treating previously treated unresectable or metastatic microsatellite instability-high or deficient mismatch repair colorectal cancer in China

Abstract: ObjectiveThe aim of this study was to investigate the cost-effectiveness of serplulimab versus regorafenib in previously treated unresectable or metastatic microsatellite instability-high (MSI-H)/deficient mismatch repair (dMMR) colorectal cancer in China.MethodsFrom the perspective of China’s health-care system, a Markov model with three health states (progression free, progression, death) was developed for estimating the costs and health outcomes of serplulimab and regorafenib. Data for unanchored matching-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Their study findings indicated that fruquintinib is the more cost-effective option, as it is associated with an increase of approximately 0.05 quality-adjusted life years (QALYs) and results in a cost saving of about $11,454. Ma Y et al 18 developed a three-state Markov model to estimate the costs and health outcomes of serplulimab and regorafenib in China. They concluded that serplulimab is more cost-effective than regorafenib for patients with previously treated metastatic colorectal cancer (mCRC) in China.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Their study findings indicated that fruquintinib is the more cost-effective option, as it is associated with an increase of approximately 0.05 quality-adjusted life years (QALYs) and results in a cost saving of about $11,454. Ma Y et al 18 developed a three-state Markov model to estimate the costs and health outcomes of serplulimab and regorafenib in China. They concluded that serplulimab is more cost-effective than regorafenib for patients with previously treated metastatic colorectal cancer (mCRC) in China.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 5 , most studies (11 out of 13) performed a sensitivity analysis to evaluate the uncertainty and robustness of the model, of which three studies adopted one-way and probabilistic sensitivity analyses 15 , 17 , 24 Three studies conducted univariate and probabilistic sensitivity analyses 14 , 16 , 19 Two studies used scenario analysis based on one-way and probabilistic sensitivity analyses; 18 , 20 one study used scenario analysis based on univariate and probabilistic sensitivity analyses, 13 the rest employed one-way sensitivity analyses and probabilistic sensitivity analyses, respectively. 23 , 25 The sensitivity analysis results revealed that drug prices, baseline utility value, and exposure to regorafenib exerted the most significant influence on the ICER.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations